Murid herpesvirus-4 exploits dendritic cells to infect B cells. - Miguel Gaspar (Public Library of Science (PLoS), 2011)
Dendritic cells (DCs) play a central role in initiating immune responses. Some persistent viruses infect DCs and can disrupt their functions in vitro. However, these viruses remain strongly immunogenic in vivo. Thus what role DC infection plays in the pathogenesis of persistent infections is unclear. Here we show that a persistent, B cell-tropic gamma-herpesvirus, Murid Herpesvirus-4 (MuHV-4), infects DCs early after host entry, before it establishes a substantial infection of B cells. DC-specific virus marking by cre-lox recombination revealed that a significant fraction of the virus latent in B cells had passed through a DC, and a virus attenuated for replication in DCs was impaired in B cell colonization. In vitro MuHV-4 dramatically altered the DC cytoskeleton, suggesting that it manipulates DC migration and shape in order to spread. MuHV-4 therefore uses DCs to colonize B cells.